The Overgrounds and Undergrounds of Pure and Applied Science: Cosmic Collisions and Industrial Collusion - Jamie Allen (Media Theory, 2018)
Archeology and geology are presumed to be â€œpureâ€ knowledge practices, curiosity-driven investigations of the material histories of humankind and the Earth. Underwritten by Enlightenment techniques and tropes, such as clarity, organisation, cleanliness and illumination, there is in all the sciences a similar drive and imaginary toward a valuation of purity, against application, in all the sciences. These practices of observation, sampling, inscribing, analyzing and publishing are, of course, much messier than we sometimes imagine. What other sciences might be possible, were we more sensitive to the complicity of specific material practices as collusive affairs, amalgams of the pure and the applied, the clean and the messy, the ecological and the infrastructural, of light and shadow, of overground and underground?